On the Sensitivity of Mechanical Properties of Woven-Fabrics to the Draping Process: Static and Dynamic Assessment Through a CAE-Based Approach - Treviso, Alessandra; Farkas, Laszlo; Mundo, Domenico; Tournour, Michel (Applied composite materials, 2016)
Manufacturing processes are often considered the final stage of the design. As a matter of fact, it is during the manufacturing that material properties are ultimately determined. This is especially true for composite materials, whose manufacturing processes are often lowly automated and thus subject to the low repeatability of manual operations. Manufacturing simulations tools are becoming available to support the definition of the manufacturing process and assess the manufacturability of composite parts. The present paper proposes a reversed approach to the laminate design process which starts from the manufacturing simulation in order to quantify the impact of the process on the mechanical properties of the as-produced part. An automotive component is chosen and different woven-fabrics structures are considered to determine their sensitivity to the shearing phenomenon. Homogenization of material properties is performed on a local basis, depending on the local geometry modifications undergone by the reinforcement. Stiffness is then predicted through both static and dynamic analysis. In order to prove the effectiveness of the approach, the obtained results are compared to classic laminate modelling.